UV-VIS AND FLUORESCENCE INVESTIGATION OF SOME POLY(ACRYLIC) GELS - TODICA, Mihai; ȘTEFAN, Răzvan; POP, Cornel Viorel; PAPUC, Ionel; STAN, Oana; OLAR, Loredana Elena (Studia Universitatis Babeș-Bolyai Chemia, 2015)
Poly(acrylic) gels, (PAA), with polymeric concentrations 0.5, 1 and 1.5%, in aqueous state and neutralized with triethanolamine, (TEA), were investigated by UV-VIS and fluorescence methods. Such gels are suitable to obtain biocompatible matrices for some medical drugs. The aqueous gel with 1% PAA concentration shows an important absorption at 214 nm. At 1.5% PAA concentration the absorption increases and the peak shifts slowly to 212 nm. The absorption increases after neutralization and the maximum of absorbance shifts to 200 nm. Excitation of aqueous gels at 250, 270 and 290 nm is followed by two important fluorescence transition centered at 320 and 405 nm. The position of the fluorescence peaks is influenced by the polymeric concentration and by the neutralization. The UV-VIS and fluorescence investigations indicate some conformational changes determined by the neutralization.